The relationship between health expenditure indicators and economic growth in OECD countries: A Driscoll-Kraay approach - Beylik, Umut; Cirakli, Umit; Cetin, Murat; Ecevit, Eyyup; Senol, Osman (Frontiers in Public Health, 2022)
The main purpose of the study is to examine the relationship between health expenditure indicators and economic growth in OECD countries. In this context, health expenditures and economic indicators data of 21 OECD countries were analyzed by the Driscoll-Kraay standart error approach within the scope of panel data analysis. While Gross Domestic Product (GDP) and income per capita were used as dependent variables, the amount of out-of-pocket expenditure, per capita health expenditure, the amount of public health expenditure, the ratio of drug expenditures to gross domestic product, the share of current health expenditures in GDP were used as independent variables. According to the results, in the model where GDP level was used as the dependent variable, all health expenditure indicators were positively related to the economic growth. In the model where the per capita income variable is the dependent variable, it is seen that the increase in out-of-pocket expenditures has a decreasing effect on the per capita income level, while the increase in public expenditures has an increasing effect on the per capita income level. Concludingly, it is possible to say that that public resources allocated to health services play an important role in the economic growth